If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 * 0 + 7y = -56 Multiply -8 * 0 0 + 7y = -56 Anything times zero is zero. 0 + 7y = -56 Remove the zero: 7y = -56 Solving 7y = -56 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '7'. y = -8 Simplifying y = -8
| -3.6x-5.9=1.3 | | y=12x+1 | | 4x+5=85-4x | | bx+gy=j | | 268-3x=42x+23 | | q+0.3=-1.1 | | 9-8x=28-15x | | -4v-3=0 | | (4x+1)(6-2x)=x(4-8x) | | 3x+33=10x-51 | | -9v-8=12 | | -10=9v-1 | | -8x+7y=-56 | | 0.8+9.9=6.3 | | -3z+1=-17 | | 0=4w-28 | | 3(x+4)=22-x | | (3x-3x)4x=2 | | 0=2w-16 | | 4x-3=10-x | | 5*2.6=r | | 5-3y=19 | | 0=-4x-7 | | (x-2)(x-3)=0 | | 14-3a=4 | | 7-3x=3x-2 | | -2x++4=5-3x | | -8x+7*0=-56 | | 12-2x=3x+4 | | 10-3x=3x-2 | | 3x-7=13-2x | | 9x-2=28-x |